Application of the probabilistic technologies to power plant design; IOP Conference Series: Materials Science and Engineering; Vol. 1019 : 14th International Forum on Strategic Technology (IFOST 2019) - Krivova L. V. Lyudmila Vladimirovna (2021, 2021)
Title screen